2022
DOI: 10.1186/s12913-022-08109-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and perceptions of a nursing discharge plan among nurses from different healthcare settings in Spain

Abstract: Purpose The exchange of information between different healthcare settings through a nursing discharge plan is essential for safe care. However, the factors contributing to achieving the most efficient exchange have not been well studied. This study aimed to evaluate and explore the perceptions of a nursing discharge plan from the perspective of nurses in different healthcare settings. Methods A mixed methods approach comprising a specifically desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Our results can therefore be considered positive in view of the large body of literature confirming the effectiveness of motivational interviewing for numerous outcomes and circumstances, including primary care [ 43 , 44 ] and chronic conditions [ 45 ]. The fact that social dimension resources were rated less positively would suggest that patients’ social problems tend to be overlooked [ 46 , 47 ], as confirmed by other studies of nursing programmes [ 6 ]. Health education resources were rated as moderate, suggesting that further efforts in this area are necessary, given the key role of health education in the community management of chronic diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our results can therefore be considered positive in view of the large body of literature confirming the effectiveness of motivational interviewing for numerous outcomes and circumstances, including primary care [ 43 , 44 ] and chronic conditions [ 45 ]. The fact that social dimension resources were rated less positively would suggest that patients’ social problems tend to be overlooked [ 46 , 47 ], as confirmed by other studies of nursing programmes [ 6 ]. Health education resources were rated as moderate, suggesting that further efforts in this area are necessary, given the key role of health education in the community management of chronic diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 78%
“…This study identified several facilitators of ARES-AP use, including the following: the organized structuring of information, which enhances tracking and understanding of individual care needs; the inclusion of evidence-based guidelines, which ensures safety and customization; improved record-keeping, which fosters interprofessional communication and care continuity; heightened recognition of the vital role of nurses in managing chronic diseases; and greater nurse autonomy in decision-making and care provision. These facilitators underscore the potential benefits of ARES-AP in terms of improved organization, safety, and efficiency, and also in recognizing nursing contributions to chronic care, documented as essential for this patient population [ 6 , 55 ]. Previous studies have reported dissatisfaction with standardized care plan programmes, particularly arising from a lack of consensus as to care plan structure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation and perceptions of a nursing discharge plan among nurses from different healthcare settings in Spain Reig-Garcia et al (11) Percepciones variadas sobre la efectividad de planes de alta en enfermería, con falta de coordinación entre hospital y atención domiciliaria para adultos mayores hospitalizados.…”
Section: Título Autor(es) Hallazgounclassified